ARTICLE TITLE: THE ACTUALITY AND SIMILARITY OF ENGLISH, UZBEK, AND RUSSIAN PROVERBS (SCIENCE TIME JOURNAL, 2025)
This article examines similarities among English, Uzbek, and Russian proverbs, demonstrating remarkable convergence in themes such as patience, work ethic, and friendship despite cultural differences. The study reveals how universal human experiences produce parallel expressions of wisdom while maintaining unique linguistic and cultural characteristics. Historical exchanges through the Silk Road and Russian-Central Asian contact contributed to these parallels. The continued relevance of these proverbs in modern society underscores their enduring value as bridges between cultures and generations.